Pengaruh Terpaan Informasi Produk dan Promosi Penjualan Terhadap Minat Menggunakan BRT Trans Semarang - Hilal Al Roshid, Fhatwa; Naryoso, Agus; Setyabudi, Djoko (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This research examines the influence of product information exposure and sales promotion on the intention to use BRT Trans Semarang. Although BLU UPTD Trans Semarang continues to disseminate product information and sales promotions through various media, BRT Trans Semarang has not been able to reach its monthly passenger target. This research aims to understand the effect of exposure to product information and sales promotions on the intention to use BRT Trans Semarang using Information Integration Theory and Cognitive Response Approach Theory. The sampling technique is non-probability sampling with a total sample of 100 respondents who are people who live in Semarang City and know the product information of BRT Trans Semarang, and have seen the sales promotion of BRT Trans Semarang. Through simple regression analysis techniques to test the first hypothesis and second hypothesis of the study, it was found that there is an influence between exposure to product information on intention to use BRT Trans Semarang as evidenced by a significance value of 0.002 which is smaller than 0.05 and a coefficient value of 0.424 so that the first hypothesis is accepted. This means that the higher the exposure to product information, the higher the consumer interest in using BRT Trans Semarang. Then the second hypothesis test shows that there is an influence between exposure to sales information on intention to use BRT Trans Semarang as evidenced by a significance value of <0.001 which is smaller than 0.05 and a coefficient value of 0.590 so that the first hypothesis is accepted. This means that the higher the exposure to sales promotion, the higher the consumer intention to use BRT Trans Semarang